Electrosynthesis of zirconia, zinc and iron supported HY zeolite-based catalysts for enhanced photodecolorization of dyes [electronic resource] - Norzahir Sapawe, 1986-, author (2013)
Thesis (Ph.D (Kejuruteraan Kimia)) - Universiti Teknologi Malaysia, 2013